2002
DOI: 10.1063/1.1445102
|View full text |Cite
|
Sign up to set email alerts
|

Electron–phonon coupling in negatively charged acene- and phenanthrene-edge-type hydrocarbon crystals

Abstract: Vibronic interaction and its role in the occurrence of possible superconductivity in the monoanions of phenanthrene-edge-type aromatic hydrocarbons are studied. The vibrational frequencies and the vibronic coupling constants are computed and analyzed and the electron-phonon coupling constants are estimated. The results for phenanthrene-edge-type hydrocarbons are compared with those for acene-edge-type hydrocarbons. The lowest frequency mode and the C-C stretching modes of 1400-1600 cm Ϫ1 afford large electron-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 52 publications
(24 reference statements)
5
57
0
6
Order By: Relevance
“…show that the C-C stretching A 1 mode of 1,434 cm − 1 (in monoanion of phenanthrene, 7 cm − 1 downshift from 1441 cm − 1 in the pure phenanthrene) strongly coupled to the a 2 LUMO in phenanthrene and has large electron-phonon coupling constants in the monoanion of phenanthrene 29 . The linewidth of the modes are obviously increased in K-and Rb-doped samples.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…show that the C-C stretching A 1 mode of 1,434 cm − 1 (in monoanion of phenanthrene, 7 cm − 1 downshift from 1441 cm − 1 in the pure phenanthrene) strongly coupled to the a 2 LUMO in phenanthrene and has large electron-phonon coupling constants in the monoanion of phenanthrene 29 . The linewidth of the modes are obviously increased in K-and Rb-doped samples.…”
Section: Resultsmentioning
confidence: 99%
“…Such a broadening of the modes arises from the electron-phonon interaction 28 . Kato et al have studied the electron-phonon coupling and predicted occurrence of possible superconductivity in negatively charged phenanthrene-edge-type hydrocarbon crystals based on the BCS theory with strong electron-phonon coupling 29 . They found that the strength of electron-phonon coupling and T c s have relevance to the molecular size and the molecular edge structures, and T c and electron-phonon coupling constants decrease with increasing the molecular size.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the feature of "armchair" edge type, which is regarded as a key factor of superconductivity in such a system, is shared in the hydrocarbon superconductors in contrast to the "zigzag" edge type. 4,6,8,13 Hydrocarbon superconductors are also a low-dimensional system with strong electron-phonon and electron-electron interactions, and both of which may be involved in superconductivity as suggested by some theoretical works.…”
Section: -3mentioning
confidence: 99%
“…Refs. [9,28,56,58,59,60,61]). Without going through a review of all the extensive theoretical literature on the subject, we highlight in Fig.…”
Section: A Paradigmatic Modelmentioning
confidence: 99%